Case report: A case of recurrent cervical cancer with bronchial and esophageal metastases presenting with hemoptysis and dysphagia - Yu, Xiao; Dong, Shixiang; Wang, Wenjie; Sun, Xin; Wang, Yankui; Yu, Fengsheng (Frontiers in Oncology, 2024)
Abstract Background: The treatment outcomes and prognosis for recurrent cervical cancer are generally poor, with a 5-year survival rate of only 10-20%. Case presentation: In this case, the patient, a young woman, experienced a recurrence five years after the initial treatment of cervical cancer. Her primary symptoms were hemoptysis and dysphagia, indicative of hilar and mediastinal lymph node metastasis, with further involvement of the bronchus and esophagus. Additionally, the patient also presented with tumor-associated dermatomyositis. Following combined treatment with albumin-bound paclitaxel, carboplatin, bevacizumab, and cadonilimab, the patient's tumor was effectively controlled.